If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 6x = 3x + 23 Reorder the terms: -10 + 6x = 23 + 3x Solving -10 + 6x = 23 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -10 + 6x + -3x = 23 + 3x + -3x Combine like terms: 6x + -3x = 3x -10 + 3x = 23 + 3x + -3x Combine like terms: 3x + -3x = 0 -10 + 3x = 23 + 0 -10 + 3x = 23 Add '10' to each side of the equation. -10 + 10 + 3x = 23 + 10 Combine like terms: -10 + 10 = 0 0 + 3x = 23 + 10 3x = 23 + 10 Combine like terms: 23 + 10 = 33 3x = 33 Divide each side by '3'. x = 11 Simplifying x = 11
| .6666(5x)=3x+2 | | -8y+6+9x=-17+y | | (4x+18)+(2x)=180 | | 2x+2(-3x+2)=48 | | 7x^2=-8 | | -4.5x+12.3=-23 | | H/4=3.1 | | -5x+3=x-12 | | 2/3(x+1)=4/9x+14/9 | | x-10+3x-6= | | -2d=-d+10 | | xy(xy-u)= | | .75x+4.50=1.25x+2.50 | | 4k=3.6 | | 1/25:3=x:12 | | sinx=0.927 | | 3k=8+4k | | 2w=3w+10 | | -6=x-14+7x | | .5(6x+10)=20 | | q+70=55 | | -35-x=31+5x | | 3t+3=6t+9 | | (5x^2+1)(6x^2+4)=1 | | G/3=3.9 | | 3(x-5)-4(2x-3)=7 | | (2y+3y)2= | | x-.85x=32.89 | | 6a-10+5a=6a+20 | | 5+1.5(2m-1)=0.5 | | 5n+35+50=160 | | 58=1/2-x |